1998
DOI: 10.3171/jns.1998.89.4.0559
|View full text |Cite
|
Sign up to set email alerts
|

Detection of soluble E-selectin, ICAM-1, VCAM-1, and L-selectin in the cerebrospinal fluid of patients after subarachnoid hemorrhage

Abstract: Adhesion molecules are known to be involved in white cell adherence to the endothelium and subsequent diapedesis and migration in which a role in initiation of tissue damage is postulated. The authors have demonstrated the elevation of three adhesion molecules, with severely elevated levels of E-selectin seen in patients who later develop vasospasm. A correlation with a role of vascular adhesion molecules in the pathogenesis of cerebral vasospasm is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(98 citation statements)
references
References 51 publications
4
91
0
2
Order By: Relevance
“…There was no statistically significant correlation between E-selectin concentrations and the clinical profile of the patients, consistent with previous human SAH studies related to E-selectin (35,36). Nevertheless, we think that this may be due to the small number of patients studied here.…”
Section: Selectins In Subarachnoid Hemorrhagesupporting
confidence: 69%
See 1 more Smart Citation
“…There was no statistically significant correlation between E-selectin concentrations and the clinical profile of the patients, consistent with previous human SAH studies related to E-selectin (35,36). Nevertheless, we think that this may be due to the small number of patients studied here.…”
Section: Selectins In Subarachnoid Hemorrhagesupporting
confidence: 69%
“…The role of CAMs, principally selectins, in SAH is less clear and few studies have investigated the changes in selectin molecules in aneurysmal SAH (35,36). Polin et al (35) showed marked elevation of soluble forms of Eselectin in the CSF of 17 patients with ruptured SAH compared with levels in the CSF of 16 controls, patients with unruptured aneurysms, and patients tested months after the occurrence of SAH. In addition, 3 patients with angiographically demonstrated VS showed higher levels of E-selectin than the average for all other SAH patients.…”
Section: Selectins In Subarachnoid Hemorrhagementioning
confidence: 99%
“…This observation suggests that the recruitment of inflammatory cells into the subarachnoid environment may play an important role. Three adhesion molecules (E-selectin, ICAM-1, VCAM-1) were found to be elevated in CSF in patients having recently suffered an aneurismal SAH, with severely increased levels of E-selectin in those who later developed clinical VS (218). Expression of ICAM-1 was found to be increased in rat basilar artery not only in the endothelial layer but also in the media at 2 -5 days after SAH (219).…”
Section: Adhesion Molecule Expressionmentioning
confidence: 91%
“…This may result in the transmigration of T-cells and monocytes into the vessel wall (De Martin et al, 2000). In addition, both NF-kB and VCAM-1 have been shown to be involved in the pathogenesis of CVS after SAH (Kaynar et al, 2004;Polin et al, 1998;Zhou et al, 2007). The intracellular Ca 2 + concentration regulates the function of the endothelial barrier between blood and the surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%